Pengaruh Model Pembelajaran Conceptual Understanding Procedures (CUPs) Dengan Teknik Problem Solving Terhadap Penguasaan Konsep Fisika Peserta Didik Di SMAN 7 Mataram - Charisma Permadi Zulmi; Hairunisyah Sahidu; Jannatin 'Ardhuha (Department of Physics Education, Universitas Mataram, 2019)
This study aims to determine the effect of the learning model of conceptual understanding procedures (CUPs) with problem solving techniques on mastering the concept of physics of students for optical instrument material inÃÂ SMAN 7 MataramÃÂ in the academic year 2018/2019. This type of research used quasi-experimental design with untreated control group design with pre-test and post-test. The population is all students of ÃÂ XI MIPA classÃÂ with taking the research sample using purposive sampling technique, so that students ofÃÂ XI MIPA 3 class were selected as the experimental class andÃÂ XI MIPA 2 class as the control class. Data collection techniques used the initial test (pre-test) and final test (post-test) with multiple choice questions as many as 20 items. To test the research hypothesis used parametric statistical tests, namely the t-test with pre-test and post-test. From the calculation results obtained by the value of t-count of 4.42 which value is greater than t-table which is 2.008 at a significant level of 5%, so it can be concluded that the null hypothesis (H0) is rejected. Thus, there is the influence of the learning model of conceptual understanding procedures (CUPs) with problem solving techniques on mastering of physics concepts of students of XI MIPA class at SMAN 7 Mataram in the academic year 2018/2019.